Stixis suaveolens (Roxb.) Fruit Extract Deciphered Antidepressant and Antidiarrheal Effects via In vivo Approach (Bangladesh Pharmaceutical Journal, 2023)
Depression is a pervasive psychiatric disorder worldwide and diarrhea is considered a leading cause of preventable death for infants and children in developing countries. The current study was done to assess in vivo activities of crude methanol extract of Stixis suaveolens fruit, focusing on antidepressant and antidiarrheal effects. The effect on central nervous system (CNS) was examined by recording the onset of sleep and total sleeping time. Besides, castor oil-induced diarrhea in the mice model was followed while evaluating the antidiarrheal effects. Significant (p